Set Covering Model in Solving Multiple Cutting Stock Problem - Sisca Octarina; Devi Gusmalia Juita; Ning Eliyati; Putra Bahtera Jaya Bangun (Science and Technology Indonesia, 2020)
Cutting Stock Problem (CSP) is the determination of how to cut stocks into items with certain cutting rules. A diverse set of stocks is called multiple stock CSP. This study used Pattern Generation (PG) algorithm to determine cutting pattern, then formulated it into a Gilmore and Gomory model and solved by using Column Generation Technique (CGT). Set Covering model was generated from Gilmore and Gomory model. Based on the results, selected cutting patterns in the first stage can be used in the second stage. The combination of patterns generated from Gilmore and Gomory model showed that the use of stocks was more effective than Set Covering model.